Production of RAFT imprinted smart hydrogel particles in a continuous flow micro-reactor - Machado, Carla (2014)
Feasibility of the production of RAFT imprinted smart hydrogel particles in continuous flow micro-reactor is here showed. Microfluidic continuous operation was combined with RAFT polymerization and molecular imprinting tecniques involving selected template molecules. New strategies for the production of advanced materials with tailored properties are thus developed. Particles syntetized in the continuous flow micro-reactor (set-up scheme depicted in the graphical abstract) were purified and characterized using different techniques, namely batch and continuous drugs adsorption and release processes. Particles were packed in small columns allowing the quick testing of these materials using frontal analysis. Therefore, the usefulness of these particles in biotechnology and biomedicine is likely.